Severe hypercalcaemia in B-cell lymphoma: combined effects of PTH-rP, IL-6 and TNF. Issue 889 (1st November 1999) - Daroszewska, Anna; Bucknall, Roger C; Chu, Patrick; Fraser, William D
Abstract : Hypercalcaemia as the only manifestation of B-cell lymphoma is seen very rarely. Its pathophysiology is heterogenous and not well understood. We report a 73-year-old man who presented with severe hypercalcaemia before any signs of malignancy became evident. He was diagnosed with a B-cell lymphoma on bone marrow trephine biopsy. The hypercalcaemia was associated with high plasma concentrations of parathyroid-hormone-related protein, interleukin-6 and tumour necrosis factor. Our patient had markedly increased osteoclast and osteoblast activity as a result of synergistic effects between these factors, with consequent severe hypercalcaemia. This is the first reported example of such combined effects of these factors in humans.